Qualitative methods and approaches in logistics. - Stock, James R. (International journal of physical distribution & logistics management, 2002)
Qualitative methods and approaches in logistics: part 2This issue of IJPDLM represents the second special issue on qualitativemethods and approaches in logistics. The first special issue appeared earlierthis year as No. 6. Additional papers that did not meet the deadline for these issues will appearin subsequent regular issues.